Development of blood cells analysis system with microelectrofluidic platform & image characterization - Ma'radzi, Ahmad Alabqari (Ministry of Higher Education Malaysia, 2011)
Microfluidic take advantage of the fact that liquids behave differently when in small volumes than they do in large quantities, while microelectrofluidic use the electrical potential that can manipulate the liquids. The development of blood cell analysis system comprise several microfluidic platforms such as microchannel, microseparator, micromixer and buffer. The system fabrication uses of SU-8 material for pattering purpose and glass substrate to produce cost effective sandwich structure. The developed system also known as lab-on-chip is a latest technology which become a new channel for biological research. Therefore, blood cell system is developed so that application such as early disease detection based on Red Blood Cell (RBC)-reagents interaction can be realized. The development of the platform consist of few stages; design and simulation, SU-8 fabrication and imaging systemintegration.